Intestinal myofibroblasts produce nitric oxide in response to combinatorial cytokine stimulation - Jianfeng Wu (2018)
Inflammatory bowel disease (IBD) patients display elevated levels of intraluminal nitric oxide (NO). NO can react with other molecules to form toxic compounds, which has led to the idea that NO may be an important mediator of IBD. However, the cellular source of NO and how its production is regulated in the intestine are unclear. In this study we aimed to determine if intestinal myofibroblasts produce NO in response to the IBD-associated cytokines IL-1β, TNFα, and IFNγ. Intestinal myofibroblasts were isolated from mice and found to express inducible nitric oxide synthase (iNOS) mRNA, but not endothelial NOS or neuronal NOS. Individual treatment of myofibroblasts with IL-1β, TNFα, or IFNγ had no effect on NO production, but stimulation with combinations of these cytokines synergistically increased iNOS mRNA and protein expression. Treatment with TNFα or IFNγ increased cell surface expression of IFNγRI or TNFRII, respectively, suggesting that these cytokines act in concert to prime NO production by myofibroblasts. Impairment of NF-κB activity with a small molecule inhibitor was sufficient to prevent increased expression of IFNγRI or TNFRII, and inhibition of Akt, JAK/STAT, or NF-κB blocked nearly all NO production induced by combinatorial cytokine treatment. These data indicate that intestinal myofibroblasts require stimulation by multiple cytokines to produce NO and that these cytokines act through a novel pathway involving reciprocal cytokine receptor regulation and signaling by Akt, JAK/STAT, and NF-κB. © 2012 Wiley Periodicals, Inc.